Studies in the Sociology of Population International Perspectives - Anson, Jon; Bartl, Walter; Kulczycki, Andrzej (Springer International Publishing : Imprint: Springer, 2019)
This book presents a cross section of the work and concerns of social demographers worldwide, covering a broad range of topics from social structure through population structure to social policy; from fertility and mortality through migration to the way in which organisations deal with the demographic environment in which they operate. Topics addressed also include morbidity and health profiles and transitions, as well as policies and programs concerned with these and other issues. The volume touches on some of the major links between population and societal dynamics. It addresses demographic patterns and issues from micro-level, meso-level, and macro-level perspectives and helps put into focus the past, present and future of the mutual relations between population dynamics and societal responses. With a unique introductory chapter discussing the global unevenness of population growth today, its associations with inequality and the challenges it presents for the future, and a truly international approach to social and demographic change and policy responses, this book will serve as a valuable resource for professionals and students in sociology, demography, social policy and local governance.